Methylation of ESR1 promoter induced by SNAI2–DNMT3B complex promotes epithelial–mesenchymal transition and correlates with poor prognosis in ERα‐positive breast cancers - Li, Ji‐Wei; Deng, Qiu‐Min; Zhu, Jian‐Ling; Min, Wei; Hu, Xiao‐Yi; Yu Chen, Hong‐; Luo, Zhong; Lin, Lin‐Ling; Wei, Xiao‐Long; Zhang, Yong‐Qu; Lou, Kang‐Liang; Gao, Yi‐Yang; et al. (MedComm (2020), 2023)
Estrogen receptor α (ERα) serves as an essential therapeutic predictor for breast cancer (BC) patients and is regulated by epigenetic modification. Abnormal methylation of cytosine phosphoric acid guanine islands in the estrogen receptor 1 (ESR1) gene promoter could silence or decrease ERα expression. In ERα‐negative BC, we previously found snail family transcriptional repressor 2 (SNAI2), a zinc‐finger transcriptional factor, recruited lysine‐specific demethylase 1 to the promoter to transcriptionally suppress ERα expression by demethylating histone H3 lysine 4 dimethylation (H3K4me2). However, the role of SNAI2 in ERα‐positive BC remains elusive. In this study, we observed a positive correlation between SNAI2 and ESR1 methylation, and SNAI2 promoted ESR1 methylation by recruiting DNA methyltransferase 3 beta (DNMT3B) rather than DNA methyltransferase 1 (DNMT1) in ERα‐positive BC cells. Subsequent enrichment analysis illustrated that ESR1 methylation is strongly correlated with cell adhesion and junction. Knocking down DNMT3B could partially reverse SNAI2 overexpression‐induced cell proliferation, migration, and invasion. Moreover, high DNMT3B expression predicted poor relapse‐free survival and overall survival in ERα‐positive BC patients. In conclusion, this study demonstrated the novel mechanisms of the ESR1 methylation mediated with the SNAI2/DNMT3B complex and enhanced awareness of ESR1 methylation's role in promoting epithelial–mesenchymal transition in BC. In an ERα‐positive BC cell, SNAI2 recruited DNMT3B to form a SNAI2‐DNMT3B combination and bound on the E‐box region of the ESR1 promoter to stimulate promoter methylation. The elevated ESR1 methylation resulted in a condensed chromatin state, transcriptional repression, and gene silencing of ESR1. Besides, SNAI2‐DNMT3B‐ESR1 also significantly facilitated the process of epithelial–mesenchymal transition and promoted the invasiveness of ERα‐positive BC cells.